Improving Security and Data Protection of Serverless Computing in the Cloud Environment - Singh, Sahibdeep; Singh Bhathal, Gurjit (International Journal of Computer Sciences and Engineering, 2024)
Offering scalability and cost-effectiveness, serverless computing has become a promising paradigm for managing and deploying applications in the cloud. But as serverless architectures become more widely used, security and data protection issues have taken center stage. This study investigates techniques and approaches to improve serverless computing`s security and data protection in cloud environments. It looks at a number of serverless architecture-specific security issues, including function-level vulnerabilities, the shared responsibility paradigm, and the possibility of data disclosure. The study also looks into best practices and current security techniques, such as access control, encryption, monitoring, and compliance procedures, to help address these issues. This presentation offers an overview of the current security situation in serverless computing through an extensive examination of the literature and case studies.Organizations can take use of serverless computing`s advantages while maintaining the privacy, availability, and integrity of their data and apps by resolving these problems.